Pregnant women's perception of fetal movement - Nurul Komariah; Sari Wahyuni (Institute of Computer Science (IOCS), 2023)
The majority of women who experienced stillbirth felt a decrease in fetal movement before diagnosis. The most frequently reported change was a decrease in perceived fetal movement. Indeed, reduced fetal movement has long been associated with adverse pregnancy outcomes such as impaired fetal growth and stillbirth. The role of the mother is very important in assessing the movement of the fetus. Factors that influence the mother in calculating her fetal movement are the mother's perception, mother's knowledge and the forgetting factor. Descriptif Design, purposive sample, 30 Samples, analyze distribution frequency. Result more than half of the respondents strongly agree with each of the statements above. Pregnant women have a good perception of fetal movement. Every pregnant woman must count fetal movements and when they find that their fetal movements are lacking, immediately go to the hospital. This research is limited to the mother's perception of fetal movement. Future researchers to study about what factors influence pregnant women in calculating their fetal movements.